87Sr/86Sr ratios in shallow and deep aquifers and thermal water from the eastern boundary fault of the northern upper Rhine Graben at the Heidelberg Basin, Germany: 15th Water-Rock Interaction International Symposium, WRI-15 - Schmidt, Gerhard; Al Najem, Sami; Isenbeck-Schröter, Margot; Freundt, Florian; Kraml, Michael; Eichstädter, René; Aeschbach, Werner (Procedia earth and planetary science, 2017)
87Sr/86Sr ratios have been used as a tracer of fault-controlled fluid ascent into shallow aquifers at the Western Boundary Fault (WBF) of the northern upper Rhine Graben in Germany, a major rift system of the European continent. The 87Sr/86Sr ratios and Sr contents from the Quarternary groundwater conducting sediments of the uppermost aquifer increase with decreasing distance to the WBF. The 87Sr/86Sr ratios and Sr contents of the shallow groundwater range from 0.70877 to 0.71022 and 0.41 to 2.30 mg/l, respectively. The Strontium isotope ratios are important tracers of hydrological processes such as water-rock interaction and groundwater mixing at active faults and thus a powerful geochemical tool for the detection of the ascent of deep fluids at hydraulically active segments of faults and its mixing with shallow recharged groundwater.
Im Zusatz zum Titel sind die Zahlen hochgestellt
Gesehen am 15.03.2017
Keywords: Konferenzschrift